Process synthesis and plantwide control of intensified extractive distillation with preconcentration for separating the minimum-boiling azeotropes: A case study of acetonitrile dehydration - Cui, Chengtian; Zhang, Qingjun; Zhang, Xiaodong; Sun, Jinsheng; Chien, I-Lung (Separation and purification technology, 2022)
•An improved systematic process synthesis method for ED with preconcentration.•Investigation of dynamics and control of potentially beneficial ED processes.•New robust control structures are developed based on temperature measurements.•Decoupling temperature loops to improve dynamic control performances.•Good quality control tackling throughput and composition disturbances up to 20 %. An investigation of the process synthesis and plantwide control of energy saving extractive distillation with preconcentration to produce anhydrous acetonitrile with ethylene glycol as a heavy entrainer is reported. In the process synthesis, process intensification introduces stripping column modification, heat integration, thermal coupling, vapor recompression, liquid side stream, and dividing wall column. These measures achieve significant reductions in energy costs of more than 30 % and the total annual cost of approximately 20 % as compared to the base case. The subsequent proposal of robust plantwide control structures brings about stable regulatory control when large ± 20% disturbances of throughput and composition are introduced. These control structures feature several decentralized proportional-integral temperature controller loops without composition measurements. The dynamic responses indicate that the control properties of complex arrangements can be comparable to those of a regular sequence, however, the intensified arrangements have the potential to offer significant energy savings.